2014
DOI: 10.5964/ejop.v10i2.714
|View full text |Cite
|
Sign up to set email alerts
|

Role Stress and Work Engagement as Antecedents of Job Satisfaction: Results From Portugal

Abstract: With more organizations looking for employees who take initiative and respond creatively to the challenges of the job, engagement becomes important at both individual and organizational levels. Engaged employees are generally more satisfied with their work, committed and effective at work. According to the JDR model (Schaufeli & Bakker, 2004), engagement may be produced by two types of working conditions: job demands (i.e., role stress) and job resources (i.e., self-efficacy). This study examines the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 20 publications
10
40
1
14
Order By: Relevance
“…Suharti and Suliyanto (2012) reported an effect of employee engagement on employee loyalty. Moura et al (2014) found that both role stress and employee engagement were significant predictors of job satisfaction. Ram and Prabhakar (2011) confirmed the hypothesis that employee engagement prompts organizational outcomes such as job satisfaction and involvement.…”
Section: Employee Engagement Consequencesmentioning
confidence: 96%
See 1 more Smart Citation
“…Suharti and Suliyanto (2012) reported an effect of employee engagement on employee loyalty. Moura et al (2014) found that both role stress and employee engagement were significant predictors of job satisfaction. Ram and Prabhakar (2011) confirmed the hypothesis that employee engagement prompts organizational outcomes such as job satisfaction and involvement.…”
Section: Employee Engagement Consequencesmentioning
confidence: 96%
“…Coetzee and De Villiers (2010) highlighted the significance of employee engagement in employee satisfaction. Similarly, Orgambídez-Ramos, Borrego-Alés, and Mendoza-Sierra (2014) and Moura, Orgambídez-Ramos and Gonçalves (2014) regard engagement as a construct that is an antecedent of job satisfaction. Saks (2006) draws attention to the inputs and outputs of employee engagement that result in engaged employees.…”
Section: Introductionmentioning
confidence: 99%
“…Cuando los profesionales de enfermería se sienten engaged en el trabajo, muestran mayores niveles de desempeño en el trabajo y valoran de un modo mucho más positivo las tareas que realizan. En consecuencia, valoran positivamente su contexto de trabajo manifestando mayores niveles de satisfacción en el trabajo (11)(12)(13)(14)16) .…”
Section: Discussionunclassified
“…Dado que los empleados engaged sienten que el trabajo que realizan es importante y muestran un mejor desempeño en sus tareas, estos valoran positivamente la función que realizan y experimentan mayores niveles de satisfacción. Diversos estudios han mostrado relaciones positivas y significativas entre el engagement y la satisfacción laboral con muestras de diversas ocupaciones (11)(12)(13)(14) , y con muestras de personal de enfermería (15,16) .…”
Section: Introductionunclassified
“…Therefore, it is significant to recognize the conception of engagement and its possible consequence. According to (Moura, et al, (2014), engagement is a belief that demonstrates individual's strength of attachment to an organization. The purpose of this study is to identify the relationship between work engagements with job satisfaction in private universities in Kurdistan.…”
Section: Introductionmentioning
confidence: 99%